The power of two / Akmal Farid Mohamed Azzahar - Mohamed Azzahar, Akmal Farid (Universiti Teknologi MARA, Kedah, 2025)
lnspideo, a prestigious animation studio founded in 2002 and based in Petoling Joyo, Selongor, Malaysia, is renowned for its forward-thinking approach to animation. Known for its commitment to excellence, the studio hos established itself as a leader in the global animation industry. lnspideo 's portfolio spans a wide variety of genres and styles, each showcasing their dedication lo high-quality storytelling. The Power of Two, their latest project, is on exciting 2D animation that combines traditional Maloy culture and mythology with a reimogined, Westernstyle djinn. The animation follows twin brothers, Zain and Ryon, who must confront Azoroth, a djinn that grants twisted wishes with deadly consequences. The brothers, armed with a sword and shield and dressed in silot-inspired boju meloyu, face a dork force that preys on human desires to gain the power of infinite wishes. The Power of Two introduces a fresh perspective on djinn mythology, highlighting the brothers' bond as they attempt lo stop Azoroth's dangerous pion. As Zain and Ryon journey deeper into the mystery, they uncover secrets that reveal Azoroth's true nature and the weight of his power. The film explores universal themes of sacrifice, loyalty, and the dangers of unchecked ambition while celebrating Malaysia's rich cultural heritage. The brothers' journey becomes a powerful metaphor for unity, resilience, and the importance of safeguarding what is truly valuable. The Power of Two transcends the boundaries of conventional animation, offering a visually stunning and emotionally resonant experience that highlights the studio's ability to innovate. The project solidifies lnspideo's position as a pioneering farce in the animation world, delivering a story that is both captivating and meaningful.